FORMATION OF NATURAL INTEGRATED ARCHITECTURE WITH HIGH-RISE BUILDINGS - , Ю. С. (Municipal economy of cities. Series: «Economy science», 2013)
The tendencies and regularities of nature integrated architecture with high-rise buildings.